Topical ozenoxacin 1% cream in impetigo: A systematic review and meta-analysis - Al-Dhubaibi, Mohammed; Bahaj, Saleh; Mohammed, Ghada; Ibrahim AbdElneam, Ahmed; Hamdan, Hamdan (Journal of Pakistan Association of Dermatologists, 2023)
Background: Impetigo is a prevalent bacterial skin infection of the youngsters. Ozenoxacin is a new quinolone topical antibacterial agent that was developed as a 1% cream for the treatment of impetigo. Objective: The purpose of this study, which included a systematic review and meta-analysis, was to map the research and present the effectiveness of ozenoxacin 1% topical cream for treating impetigo. Methods: From the beginning to the end of the study period [July 2022], a thorough search was conducted on the PubMed, Google Scholar, Cochrane library, and Science Direct databases. According to clinical judgment and bacteriological testing, relevant studies that reported the success rate of ozenoxacin 1% topical cream in treating impetigo were included. Meta-analysis was done using the open-source software "R". The odds ratio was calculated along with the 95% confidence interval. To assess the level of certainty of the generated result, the GRADEpro tool was used. Results: This systematic review as well as meta-analysis included 4 clinical trials, two from Spain and two from the United States of America, with an approx of 1,874 cases, 957 of which used ozenoxacin 1% topical cream and 917 of which used placebo treatment. The fixed effect model showed that the use of ozenoxacin 1% topical cream is more effective than the use of placebo based on clinical judgment [OR= 2.16, 95% CI (1.77 âˆ’ 2.65); P=<0.001; I2= 1%] and based on bacteriological culture testing results [OR= 4.15, 95% CI (3.08 â€“ 5.57); P=<0.001; I2= 27.5%]. There is no evidence of publication bias or heterogeneity. The generated evidence is classified as having a high level of certainty. Conclusions: With a high certainty level of evidence, this meta-analysis showed that ozenoxacin 1% topical cream effectively treats impetigo over a placebo for both children and adult patients.